2000
DOI: 10.1086/303004
|View full text |Cite
|
Sign up to set email alerts
|

The Ancestry of Brazilian mtDNA Lineages

Abstract: We have analyzed 247 Brazilian mtDNAs for hypervariable segment (HVS)-I and selected restriction fragment-length-polymorphism sites, to assess their ancestry in different continents. The total sample showed nearly equal amounts of Native American, African, and European matrilineal genetic contribution but with regional differences within Brazil. The mtDNA pool of present-day Brazilians clearly reflects the imprints of the early Portuguese colonization process (involving directional mating), as well as the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
437
9
41

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(559 citation statements)
references
References 54 publications
72
437
9
41
Order By: Relevance
“…Although these groups constitute less than 1% of the total population, 22,26 present-day Brazilians still carry alleles from the early colonization phase, as showed by mitochondrial DNA data, indicating that Indian matrilineal contribution to the total present-day Brazilian population with European origin gene pool may be as high as 33%, varying from 54% in the northern region to 22% in the south. 27 Studies of nuclear markers have shown that the overall (matrilineal and patrilineal) Amerindian contribution is lower, varying from 41% in the northern 28 to 7-11% in the southern regions. 29 Guarani and Kaingang are currently two of the most populous Amerindian groups in Brazil (41 000 and 22 000, respectively) and also the major Southern Brazilian Indian populations.…”
Section: Resultsmentioning
confidence: 99%
“…Although these groups constitute less than 1% of the total population, 22,26 present-day Brazilians still carry alleles from the early colonization phase, as showed by mitochondrial DNA data, indicating that Indian matrilineal contribution to the total present-day Brazilian population with European origin gene pool may be as high as 33%, varying from 54% in the northern region to 22% in the south. 27 Studies of nuclear markers have shown that the overall (matrilineal and patrilineal) Amerindian contribution is lower, varying from 41% in the northern 28 to 7-11% in the southern regions. 29 Guarani and Kaingang are currently two of the most populous Amerindian groups in Brazil (41 000 and 22 000, respectively) and also the major Southern Brazilian Indian populations.…”
Section: Resultsmentioning
confidence: 99%
“…This is not unexpected because, although the contemporary Brazilian population is highly admixed, there is a predominance of European alleles, especially in the formation of the genetic pool of Southern Brazil where this study was carried out. Price et al (22), for instance, have estimated that African and European ancestry corresponds to 11 and 71% of the alleles in Brazilian individuals and Alves-Silva et al (23) described a major contribution of European alleles to both mitochondrial (66%) and nuclear (79%) DNA in populations from Southern Brazil. An interesting observation is that the frequency of homozygotes for the STK15 F31I A allele (risk genotype AA) is 7-fold higher in the Asian (Chinese) populations studied so far than in the sample studied here and other European populations.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the genetic heterogeneity observed in the prevalence of these mutations in patients with HH from different ethnic groups, it was not unexpected to find a lower frequency of C282Y and H63D mutations in patients with HH from Brazil, where the population is of highly admixed origin with varying percentages of Negroid, Caucasian and Amerindian ancestries (31,32). It is therefore possible that other still unknown mutations in the HFE gene or in other loci involved in iron metabolism are related to HH in Brazilian patients.…”
Section: Discussionmentioning
confidence: 99%